2014
DOI: 10.1016/j.neuroscience.2014.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the reinstatement of ethanol seeking with ganaxolone and gaboxadol

Abstract: The endogenous neuroactive steroid allopregnanolone (ALLO) has previously been shown to induce reinstatement of ethanol seeking in rodents. ALLO is a positive allosteric modulator at both synaptic and extrasynaptic GABAA receptors. The contribution of each class of GABAA receptors in mediating reinstatement of ethanol seeking is unknown. The first aim of the present study was to determine whether ganaxolone (GAN), a longer-acting synthetic analog of ALLO, also promotes reinstatement of ethanol seeking. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Previous studies from our lab (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016) and others (Ramaker et al, 2011, 2012, 2014a, 2014b) have shown that THIP can significantly reduce voluntary ethanol consumption and operant responding for the drug. Given THIP’s high affinity for δ-GABA A Rs, these data support a possible role for these extrasynaptically located GABA A receptors in mediating this pattern of ethanol use.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies from our lab (Moore et al, 2007; Fritz and Boehm, 2014; Quoilin and Boehm, 2016) and others (Ramaker et al, 2011, 2012, 2014a, 2014b) have shown that THIP can significantly reduce voluntary ethanol consumption and operant responding for the drug. Given THIP’s high affinity for δ-GABA A Rs, these data support a possible role for these extrasynaptically located GABA A receptors in mediating this pattern of ethanol use.…”
Section: Discussionmentioning
confidence: 68%
“…A growing number of reports support inhibition mediated by extrasynaptic GABA A receptors as a target for the effects of binge alcohol intoxication and consumption (Nie et al, 2011; Ramaker et al, 2011, 2012, 2014a, 2014b; Fritz and Boehm, 2014). Unlike the classic synaptic subtype of GABA A receptors that mediate phasic inhibition following vesicular release of GABA, extrasynaptic GABA A receptors mediate a constant tonic inhibition, responding to the low to moderate concentrations of ambient GABA found in the extrasynaptic space (Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of this effect was surprising and requires further investigation. Nonetheless, other studies have previously shown that a moderate dose of THIP may result in higher locomotor activity by itself (Ramaker et al, 2012(Ramaker et al, , 2014 or in combination with EtOH (Broadbent and Harless, 1999). In contrast, THIP had a considerable depressant action in adolescent mice.…”
Section: Discussionmentioning
confidence: 90%
“…An initial increase in ethanol intake following GAN treatment is consistent with previous work using systemic ALLO or GAN, whereas an initial increase in intake was absent following THIP injection (Ford et al, 2005, 2007; Ramaker et al, 2011). Although it is not clear if the initial increase in ethanol intake following intra-NAc GAN reflects ethanol seeking, previous data have shown an increase in ethanol seeking following systemic ALLO or GAN, but not THIP injection (Janak and Gill, 2003; Finn et al, 2008; Ramaker et al, 2012, 2014). Together these studies suggest that differences in receptor pharmacology or GABA A R targets between the synthetic neuroactive steroid and direct extrasynaptic agonist may differentially alter ethanol seeking or initial ethanol intake.…”
Section: Discussionmentioning
confidence: 95%